2021
DOI: 10.1007/s40843-020-1548-x
|View full text |Cite
|
Sign up to set email alerts
|

Achieving superior performance in thermoelectric Bi0.4Sb1.6Te3.72 by enhancing texture and inducing high-density line defects

Abstract: Miniaturization of efficient thermoelectric (TE) devices has long been hindered by the weak mechanical strength and insufficient heat-to-electricity conversion efficiency of zone-melted (ZM) ingots. Here, we successfully prepared a robust high-performance p-type Bi 0.4 Sb 1.6 Te 3.72 bulk alloy by combining an ultrafast thermal explosion reaction with the spark plasma sintering (TER-SPS) process. It is observed that the introduced excess Te not only enhances the (00l)-oriented texture to ensure an outstanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 59 publications
(80 reference statements)
0
23
2
Order By: Relevance
“…[22][23][24][25] Further microstructure engineering can also improve the electrical transport properties in many ways. For example, proper grain size enlargement 8,26,27 and texturing 7,[28][29][30] can increase the chargecarrier mobility, and nano-inclusions with an appropriate band structure increase the Seebeck coefficient via the energy filtering effect. [31][32][33][34] Therefore, the power factor (PF, which is equal to sS 2 ) of powder-processed Bi 2 Te 3 -based materials has been improved to 4.0-5.0 mW m À1 K À2 , which equals those obtained using zonemelting or the Bridgman technique.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25] Further microstructure engineering can also improve the electrical transport properties in many ways. For example, proper grain size enlargement 8,26,27 and texturing 7,[28][29][30] can increase the chargecarrier mobility, and nano-inclusions with an appropriate band structure increase the Seebeck coefficient via the energy filtering effect. [31][32][33][34] Therefore, the power factor (PF, which is equal to sS 2 ) of powder-processed Bi 2 Te 3 -based materials has been improved to 4.0-5.0 mW m À1 K À2 , which equals those obtained using zonemelting or the Bridgman technique.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving high ZT values is challenging because of the strong coupling of S, σ, and κ tot (mainly κ e ). Nevertheless, great progress has been made in improving the ZT values using a variety of methods such as nanostructure engineering [8][9][10], electronic band engineering [11][12][13], energy-filtering effect [14][15][16][17], defects engineering [18][19][20][21], as well as seeking or exploring materials with intrinsically low thermal conductivity [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to maintain a high F , a moderate P should be adopted. We found the sample processed by under 20 MPa exhibited a high F of 0.8, which was much higher than that of the polycrystalline materials prepared by the traditional PM method. ,, XRD pole figures in Figure c,d further confirm that the sample of P = 20 MPa shows the strong (00 l )-oriented texture [since there are almost no other texture signs of the (015) and (110) planes]. From the SEM images of the samples processed under various pressures (Figure S4), it can be found that the lower the applied pressure, the smaller the misplaced laminated structure of the cleavage sheets and thus the higher the textured degree.…”
Section: Resultsmentioning
confidence: 68%
“…Theoretically, the in-plane carrier mobility (μ) is about 3 times as high as that of out-of-plane, while the in-plane lattice thermal conductivity (κ L ) is about 2-fold higher than that of out-of-plane . This leads to strong anisotropic TE performance, where the in-plane ZT value is remarkably better than that of the out-of-plane. , Nevertheless, in order to achieve these sharp anisotropic TE properties in polycrystalline samples, it is a prerequisite to prepare materials with a strongly textured microstructure. High textures are usually of great benefit to the transport of electrons and thus lead to an obvious increase of l e and μ. In the meantime, l ph should be diminished to obtain a lower κ L so as to mitigate the adverse contribution of electronic thermal conductivity (κ e ∝ μ) to κ t . …”
Section: Introductionmentioning
confidence: 99%